Review of in vitro drug release test method's statistical evaluation to compare dissolution profile of semisolid dosage forms - Part I - Eva Petro, Istvan Eros, Ildiko Csoka (Journal of Applied Pharmaceutical Science)
The aim of this mini-review study is to give an overview about in vitro drug release test methods statistical evaluation comparing dissolution profile of semisolids. The FDA released guidance in May 1997 entitled Scale-up and Post Approval Changes for Nonsterile Semisolid Dosage Forms (SUPAC-SS). The guidance focuses on creams, gels, lotionts and ointments. The guideline desribes in vitro dissolution tetsing as an useful final quality control (QC) tool. The aim of it is to assure batch-to-batch quality of the product. Changes are separated in 4 categories in 3 Levels (Level 1,2,3). Level 2 recommends in vitro release (IVR) testing. Although there are several in vitro drug release test methods of semisolid dosage forms, their statistical evaluation is not clarified up to this day. Our second challenge was to describe similarity and difference of these pharmaceutical dosage forms with use of similarity (f2) and difference (f1) factors. The FDA has issued these factors for solid dosage forms. Our present work deals with calling attention on the lack of statistical validated method for semisolid dosage forms.
Keywords: semisolid dosage forms,dissolution,in vitro.